2020
DOI: 10.1002/smi.3014
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and relational conditions for job crafting to occur

Abstract: This study aimed to provide a wider understanding of the determinants of job crafting by jointly considering employee well‐ and ill‐being (work engagement and exhaustion) and socio‐environmental factors (supervisor and colleague support) as possible levers to promote job crafting. A secondary goal of this research was to simultaneously explore the multidimensionality of work engagement and the potentially differentiated associations between the different facets of work engagement and job crafting behaviours. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…For example, approach crafting was found to be stimulated by social interactions with others, such as customer participation (Loi et al, 2020), and through feedback (Bizzi, 2017). Furthermore, social support from colleagues or supervisors was positively associated with seeking resources (Audenaert et al, 2020;Huyghebaert-Zouaghi et al, 2021;Kerksieck et al, 2019) and seeking challenges (Audenaert et al, 2020). With regard to avoidance crafting, Audenaert et al found that colleague support was not associated with avoidance crafting, but Huyghebaert-Zouaghi et al (2021) found that colleague support was positively associated with avoidance crafting.…”
Section: Collaborative Craftingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, approach crafting was found to be stimulated by social interactions with others, such as customer participation (Loi et al, 2020), and through feedback (Bizzi, 2017). Furthermore, social support from colleagues or supervisors was positively associated with seeking resources (Audenaert et al, 2020;Huyghebaert-Zouaghi et al, 2021;Kerksieck et al, 2019) and seeking challenges (Audenaert et al, 2020). With regard to avoidance crafting, Audenaert et al found that colleague support was not associated with avoidance crafting, but Huyghebaert-Zouaghi et al (2021) found that colleague support was positively associated with avoidance crafting.…”
Section: Collaborative Craftingmentioning
confidence: 99%
“…Furthermore, social support from colleagues or supervisors was positively associated with seeking resources (Audenaert et al, 2020;Huyghebaert-Zouaghi et al, 2021;Kerksieck et al, 2019) and seeking challenges (Audenaert et al, 2020). With regard to avoidance crafting, Audenaert et al found that colleague support was not associated with avoidance crafting, but Huyghebaert-Zouaghi et al (2021) found that colleague support was positively associated with avoidance crafting. These inconsistent findings are difficult to explain, as they may depend on the specific samples (i.e.…”
Section: Collaborative Craftingmentioning
confidence: 99%
“…The second domain of motivation and emotion includes the constructs academic motivation (Litalien et al, 2017 ; Guay and Bureau, 2018 ; Gordeeva et al, 2020 ; Howard et al, 2020 ; Kartal, 2020 ; Guay et al, 2021 ; Dierendonck et al, 2022 ), sport motivation (Appleton et al, 2016 ; Milton et al, 2018 ; Stenling et al, 2018 ; Cece et al, 2019 ; Méndez-Giménez et al, 2020 ; Rodrigues et al, 2020 ), work motivation (Burk and Wiese, 2018 ; Calkins, 2018 ; Howard et al, 2018 , 2020 , 2021 ; Gegenfurtner and Quesada-Pallarès, 2022 ), job satisfaction (Sutherland, 2020 ), affective commitment (Perreira et al, 2018 ), work engagement (Gillet et al, 2019 ; Huyghebaert-Zouaghi et al, 2021a , 2022 ), teacher engagement (Perera et al, 2018b ), student engagement (Hoi and Hang, 2021 ; Dierendonck et al, 2022 ; Tomás et al, 2022 ), basic psychological needs (Stenling et al, 2015 ; Sánchez-Oliva et al, 2017 ; Tóth-Király et al, 2018 , 2019 ; Bhavsar et al, 2019 , 2020 ; Garn et al, 2019 ; Burgueño et al, 2020a , b ; Cromhout, 2020 ; Gillet et al, 2020 ; Gucciardi et al, 2020 ; Huyghebaert-Zouaghi et al, 2021b ; Rodrigues et al, 2021 ), subjective task value (Fadda et al, 2020b ; Part et al, 2020 ), flow (Kyriazos et al, 2018b ; Gu et al, 2020 ), interest (Garn, 2017 ), locus of causality (Howard et al, 2020 ), attitudes (Deemer et al, 2014 ), purpose (Summers and Falco, 2020 ), self-efficacy (Barbaranelli et al, 2018 ; Dominguez-Lara et al,…”
Section: Resultsmentioning
confidence: 99%
“…Relational crafting. Relational crafting is the process through which individuals make specific and conscious decisions in their work routine to seek enhancing the quality of interactions with their colleagues (Huyghebaert-Zouaghi et al, 2021). We found that, by using different personal resources, more related to the social and relational sphere, such as cunning, sociability and empathy, managers claimed to be able to modify the relational boundaries of their jobs and thus enhance the quality of their relationships within the team also during challenging times as the one preceding or following the leadership team transition.…”
Section: Personal Resources and Job Craftingmentioning
confidence: 99%
“…Petrou et al, 2017Petrou et al, , 2018. Moreover, our study contributes to advancing prior research on the antecedents of job crafting (Buonocore et al, 2020;Hu et al, 2021;Huyghebaert-Zouaghi et al, 2021;Yoon et al, 2019), by exploring how perceptions of uncertainty can influence job crafting behaviors (Barclay et al, 2022;Chen and Tang, 2021). Finally, using a qualitative approach in the study of job crafting is an important methodological advancement, as research on the topic is predominantly quantitative (Zhang and Parker, 2019), therefore unable to provide in-depth insights into the process underlying the adoption of these proactive behaviors (Lazazzara et al, 2020).…”
Section: Introductionmentioning
confidence: 98%